المرأة في رسوم جواد سلیم وبیكاسو (Journal of the College of Education for Women, 2019)
There is a fact we have to admit here, first, that is art innovation, sinceits early beginnings, is mostly a male product, and causing to stir interest andattention, if it was a female one. Psychiatrist and sociologists could give us aconvincing answer or a logical explanation for that. What is really importanthere is how the male artist could review his vision to woman, what was theimpact of all these ideas and desires towards each other in their artisticproducts? Did he reflect the real role played by the woman in pushing theartist towards specific ways? Did it related to the struggle for immortality? Insearching for motherhood and life eternity and the partner to find the way tolife. We, often, find artworks showing great interest in woman to the extentthat she became a case or may be an aim that most of his works consistwhether the artwork discuss a humane issue or reviewing the beauty ofhumane figure.Jawad Salim's works were the fertile soil to study that if we simplyreviewed some of them. Picasso, as well, was not far from that if weacknowledged that only few of his works lacked the presence of woman. Forall of the above mentioned, lie the true objectives of this research to unveilthe nature of the humane and intellectual contents related to woman in Jawad and Picasso's paintings, their importance and role, their similarity anddifferences throughout their art career.The main results the researcher reached is that:1- During his blue and pink period, Picasso took the woman as a humanesymbol reflecting the Spanish reality; he shouldered the responsibilityof representing the sad nation (Pain-isolation-poverty- subjugation).2- Jawad Salim attacked in his works the oriental social traditions thatdealt with woman during the 40s, which was a reflection of hispersonal sufferings in his early life and the contradictory he livedbetween Paris and Baghdad.3- Follwing the inspiring Lorna (Jawad's wife), he switched to defendthe human woman (mother-sister-friend-wife) in her tragedy andpolitical and social struggle side by side with the man, that wasclearly shown in what we so-called (freedom period) at the end of 50swhich preceded his early death.4- During his Cubism and after that, Picasso resorted to oddity –theprimitive arts- in achieving innovative amazement. The lot offamiliarity and satisfaction exist inside him, prompted him to look forthe new, as if it is a reflection to his relation with woman.